Evaluation of the knowledge of the population of Passa Quatro - MG about Human Papillomavirus (HPV), regarding prophylaxis and clinical manifestation (Research, Society and Development, 2024)
Human Papillomaviruses (HPV) are epitheliotropic viruses that lead to the development of lesions ranging from anogenital warts to neoplasms, depending on the type of virus involved. Among the most common types are HPV 6 and 11, which are low-risk and generally associated with the emergence of condyloma acuminatum, and HPV 16 and 18, which are high-risk and commonly associated with the development of precursor cancer lesions. Objective: to analyze the degree of knowledge of the population of Passa Quatro- MG about the virus, seeking to evaluate what is know about the prophylaxis and possible clinical manifestations of the infection. Method: application of a questionnaire remotely through the Google Forms platform, to people over the age of 18. Results: levels of knowledge about the topic were high, with women presenting rates of more than 70% in all questions asked in the survey, while in the age group, although in all of them more than half claim to know what was asked, the indices were lower among those from 18 to 29 years. As far as vaccination is concerned, the majority of respondents claimed to be aware of the existence of the HPV vaccine, with rates exceeding 66.7%. Conclusion: it was found that in the gender variable, the female group presents more knowledge, while in the age range, 18 to 29 years presents the lowest rate. As regards shooling and income, the data proved insufficient for assertive analysis.